The relations between bank-funding costs, retail rates, and loan volumes. Evidence form Norwegian microdata - Arvid Raknerud; Bjørn Helge Vatne (Statistics Norway, Research Department, 2013)
In this paper, we examine two questions: i) how changes in the funding costs of banks affect retail loan rates and ii) how changes in relative loan rates between banks affect their market shares. To do so, we estimate a simultaneous system of equations model using panel data for six Norwegian bank groups. The data set consists of quarterly data for the period 2002Q1-2011Q3 and includes information on loan volumes and retail (interest) rates for loans to firms and households. The cost of market funding is represented in our analysis by the three-month money market rate and a proxy for market risk; the credit spread on unsecured senior bonds issued by Norwegian banks. Our estimates suggest that a 10 basis points increase in the market rate leads to an approximately 8 basis points increase in retail loan rates. We also find that credit demand from households is more elastic with regard to the loan rate than credit demand from businesses.
Keywords: C33; E27; E43; 330; Credit demand; Pass-through; Funding costs; Monopolistic competition; Panel data; Dynamic factor model